Bakery Product Distribution Efficiency: A Case Study of Danisy Bakery Delivery with Transportation Methods - Pamungkas, Aditya Dwi; Danisy, Ara; Ayun, Saidah Qurrota; Amamah, Risma Hanifatin (Department of Islamic Economics, Faculty of Islamic Economics and Business, Universitas Islam Negeri Sunan Kalijaga, 2024)
Distribution efficiency is very important in reducing business operational costs, especially in the food industry such as Danisy Bakery. This study uses a quantitative approach with a case study of Danisy Bakery's distribution. The data collected includes the amount of production, the destination of delivery, and the cost of transportation per unit. The calculation is carried out by applying the NWC and Least Cost methods, then compared to determine the most economical method. The results of the study show that the Least Cost method is more effective in reducing costs than NWC because it prioritizes the cheapest route, so that the allocation is more optimal. This method is recommended to improve the distribution efficiency of Danisy Bakery. This research is expected to help business actors choose a more cost-efficient distribution strategy and become an academic reference in the application of transportation methods.